2012
DOI: 10.1210/jc.2011-2209
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cells as a Source of Transcriptional Biomarkers of Childhood Obesity and Its Related Metabolic Alterations: Results of the IDEFICS Study

Abstract: These findings point toward the possibility of using the expression levels of these genes in blood cells as markers of metabolic status and can potentially provide an early warning of a future disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 18 publications
4
60
0
Order By: Relevance
“…These cells also change their gene expression in response to overweight or obesity, as evidenced in studies mainly performed in rodents . In addition, our group has shown that whole blood cells (which include the PBMC fraction) constitute a proper source of nutritional biomarkers in human studies . Based on this, PBMC can be used as a surrogate biological material to perform nutritional and obesity‐related studies without the need to use other samples more difficult to obtain.…”
Section: Introductionmentioning
confidence: 97%
“…These cells also change their gene expression in response to overweight or obesity, as evidenced in studies mainly performed in rodents . In addition, our group has shown that whole blood cells (which include the PBMC fraction) constitute a proper source of nutritional biomarkers in human studies . Based on this, PBMC can be used as a surrogate biological material to perform nutritional and obesity‐related studies without the need to use other samples more difficult to obtain.…”
Section: Introductionmentioning
confidence: 97%
“…As such studies have never been carried out in patients with gestational diabetes (GDM), we hypothesized that the development of insulin resistance and hyperglycemia during pregnancy may influence the expression of genes encoding receptors of surface ligands and immune mediators involved in NF-kB signaling pathway. To verify this hypothesis, we obtained PBMCs from women with GDM and normal glucose tolerance (NGT) during pregnancy and measured mRNA expression of genes: i) encoding receptors of surface ligands (TLR4, TLR2, TNF receptor superfamily member 1A (TNFRSF1A) and 1B (TNFRSF1B), and receptor for IL1 (IL1R1)) and mediators (IKBKB and chemokine (C-C motif) ligand 5 (CCL5)) involved in NF-kB signaling; ii) related to immunological and endothelial function and positively regulated by NF-kB (IL8, IL17 (IL17A), chemokine (C-X3-C motif) ligand 1 (CX3CL1), and intercellular adhesion molecule 1 (ICAM1)); iii) essential for cytokine receptor signaling (signal transducer and activator of transcription 1 (STAT1) and STAT2); iv) involved in inhibiting inflammatory response via negative regulation of several cytokine pathways (IL10, suppressor of cytokine signaling 1 (SOCS1), SOCS2, and SOCS3), including NF-kB signaling pathway (peroxisome proliferator-activated receptor-g (PPARG)); and v) potentially positively (dipeptidylpeptidase-4 (DPP4)) or negatively (solute carrier family 27 fatty acid transporter, member 2 (SLC27A2)) regulated by insulin resistance (25,26,27).…”
Section: Introductionmentioning
confidence: 99%
“…PBMCs are increasingly proposed for clinical diagnostic purposes as they can reflect gene expression patterns of different pathologies (1,12,56). Moreover, PBMCs have been shown to be useful for nutritional studies as they can reflect the effects of specific diets and feeding conditions (fasting/refeeding) on gene expression, which occur in key energy homeostatic tissues as liver and adipose tissue (7,9,10,16,24,41,50,55,62). In addition, PBMCs have been proposed as a potential source of obesity biomarkers (31,41) or acquired predisposition to develop obesity (30).…”
mentioning
confidence: 99%